Publishing in the Shadow of Larger Neighbours: Opportunities and Challenges of Digitisation for Small Publishing Houses in Austria and Scotland - Klamet, Anna (Knygotyra, 2020)
Trade publishing houses in small nations operate in a challenging market environment: digitisation and the spread of the internet have lowered the market entry barriers and increased the international competition. This is especially prevalent in English-language markets and increasingly so in the markets with a high English language proficiency amongst second language speakers due to the amount of English content readily available online. Moreover, traditional audiences are eroding, and global players push for multi-platform publishing for a global audience. However, the impact of digitisation on small nation publishers operating in large language markets lacks scientific exploration. Hence, the impact on small trade publishing houses in Austria and Scotland is explored through qualitative case study research. An overview of the state of the publishing industry in those nations is presented, followed by an analysis of the opportunities and challenges of publishing in an online world where borders are disappearing, thus changing the competitive situation of publishers competing with larger entities in neighbouring nations with the same language.The research found that small nation publishers are benefiting from the possibilities offered by digitisation to reach a wider readership abroad, but at the same time it is becoming increasingly difficult for these publishers and their products to stand out amongst the abundance of content online. Thus, small publishers choose market niches and collaborations to create sustainable business practices. Furthermore, these results provide a basis for further research into e-publishing in other small nations. Additional comparative research is needed to better understand the cultural specificities of small book markets and how to best support publishers in and for those nations.
Keywords: Small Nation Publishing; Trade Publishing; Europe; Austria; Scotland; Small and Medium Sized Enterprise (SME); Digital Publishing; Digitisation; Digital Disruption